Contextualization of the Constitutional Court’s Decision on Women’s Inheritance Rights in Customary and Islamic Marriages - Syahril, Muh. Akbar Fhad; Wiwin, Wiwin; M.A, A.P. Jaya Negara (Jurnal Litigasi Amsir, 2025)
This study critically analyzes the influence of legal system pluralism on the reality and reconstruction of women’s inheritance rights in customary and Islamic practices in Indonesia, highlighting the crucial role of Constitutional Court decisions. Based on the diversity of Islamic, customary, and civil law inheritance systems, this study finds that women often face structural obstacles, both due to conservative normative interpretations and the dominance of patriarchal traditions in inheritance distribution. Using normative juridical methods and an examination of Constitutional Court Decision No. 46/PUU-VIII/2010 and related jurisprudence, this study confirms a paradigm shift toward more inclusive and equitable protection for women heirs. However, the implementation of this progressive legal substance still faces cultural resistance and social obstacles that require state intervention through regulatory harmonization, law enforcement, and public education. These findings are expected to provide a foundation for reforming family law that guarantees equality and justice for women’s inheritance rights in Indonesia.